The Role of Single Nucleotide Polymorphisms (SNPs) Pvu II and Xba I and Short Tandem Repeats (STRs) (TA)n and (GT)n of Estrogen Alpha Receptor (ESRI) in Breast Cancer (BRCA) Susceptibility - Araújo, Karine Lourenzone de (2009)
Estrogen is a steroidal sexual hormone that shows effect in both male and female reproductive tracts. Its effects are mediated mainly by the α and ß isoforms of the estrogen receptor (ER α and ß), members of the superfamily nuclear receptor which controls gene expression. In fact, the gene's response to estrogen depends on many factors, including the assessment of subtypes of ER, the co-regulators, the time of exposure to estrogen and the amount of this hormone. Alternative processes (splicing) generates several variants of RNAm species of ESR1. The RNAm isoforms with distinct regions of 5' non-translated result in the expression of ESR1 protein of different sizes. It is known that the ESR1 gene has many polymorphic sites that may be responsible for such allelic variants of the protein, which may modify both function and activity of this protein and, therefore, show the observed differences of the estrogen effect on the disease development. There are several risk factors related to breast cancer (BRCA), but just recently, have the polymorphisms on the ESR1 gene been studied in this neoplasia. The single nucleotide polymorphisms (SNPs) known as Pvu II and Xba I and STRs (GT)n and (TA)n have intrigued the researcher because they are located within non-translated regions of the ESR1 gene and may also be related to BRCA. It has been noticed that such elements may interfere with this disease; however, the results are not very consistent. Nevertheless, it is important to increase the knowledge of the genetic of ESR1 because there is evidence that its properties interfere with the development of breast cancer.